FAKTOR PENYEBAB PERCERAIAN PERNIKAHAN DINI DI KELURAHAN PITAMEH KECAMATAN LUBUK BEGALUNG KOTA PADANG - Andriani, Lusi - (Bimbingan dan Konseling, 2014)
This research do through qualitative describtive approach, this approach describe of identification,fact and reality in the real life about the factor of caused by the divorce of early marriage in Pitameh LubukBegalung. The instrument of the researcher is used in this research is interview, tekhnique is used inprocessing of the datas are application, triangulation, colleaque checking/investigation from discussion,negative case analyze, member verivication, detail analyze, auditing, and analyze result naration. Theresults of the research are (1) The internal factors caused by the divorce of early marriage in Pitameh LubukBegalung Padang City are: (a) The low of education, it caused the informan comprehension level inunderstand about the important of sacred of marriage is also low, (b) The young age make the youngcouples have been not ready yet to appear many difficulties, (c) The key informan does not have mentalmature in enter on life of household such as the key informan does not have perception about the purpose,the duty and their responsibility in their household, (d) The economic factor, this factor is the hardestproblem divorce because there is no the preparation of economic while hold the marriage, it becomedispute, (e) The emotional that has not mature yet, it caused the disputes are become, the couple cannotminimaze the emotional (2) The external factor caused by the divorce of early marriage in Pitameh LubukBegalung Padang City, they are: (a) The intervention of the third person it caused the broken of householdlike negative isues expressly or not, (b) The divorce happen cause one of the cauple leave the other likeprovide/include in marriage regulations.